The Essence of Legal Protection of Personal Data of Customers In Banking Transactions - Haliwela, Nancy Silvana (SASI, 2023)
Introduction: Banks as an institution are not only required to protect customer funds but are also obliged to maintain the confidentiality of customer personal data.Purposes of the Research: This paper aims to examine the regulations governing the protection of customers' personal data and to examine the supervision and law enforcement of the protection of banking customers' personal data.Methods of the Research: This research uses normative legal research methods with a statutory approach, conceptual approach, and case approach. The statutory approach relates to legislation on personal data protection and banking. The conceptual approach relates to the concepts of banking and personal data protection. The case approach relates to cases of supervision and law enforcement of violations or crimes of personal data of banking customers.Results of the Research: The results show that regulations governing customer data protection are contained in various laws and regulations related to personal data protection and banking and other technical regulations. In addition, the study results also show that supervision of the protection of personal data of banking customers has been carried out by three institutions that have supervisory authority, namely Bank Indonesia, the Financial Services Authority, and the Deposit Insurance Corporation. Law enforcement against violations and crimes against customers' personal data still faces challenges, because although there are many cases of crimes using customers' personal data, only a few can be enforced against crimes against customers' personal data.